Nurse Case Manager Lifestyle Medicine (NCMLM) in the Type Two Diabetes patient concerning post COVID-19 Pandemic management: Integrated-Scoping literature review - Cangelosi, G.; Grappasonni, I.; Pantanetti, P.; Scuri, S.; Garda, G.; Cuc Thi Thu, N.; Petrelli, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The American Case Manager Association defines Case Management, in Lifestyle Medicine perspective, a collaborative practice between all the actors involved in the care process. The goal of this review was to evaluate the Nurse Case Manager role in Type 2 Diabetes patients, analyzing the quali/quantitative data related to Nurse Case Management programs in Lifestyle Medicine view.Study design and Methods. Three independent operators were involved in two distinct phases, applying the Prisma method, specifics PICOS and research strategies from PubMed and Cinahl. The first part integrated a Cochrane systematic review on the Specialist Nurses in Diabetes Mellitus, while the second part evaluated the Nurse Case Manager interventions in Lifestyle Medicine view.Results. The first part includes 13 studies and the second 6. The glycemic control was improved in the Nurse Case Manager groups in Lifestyle Medicine perspective. Good results were appreciated in secondary outcomes: lipid profile, Body Mass Index, quality of life and stress management. The results for the management of self-care and adherence to Lifestyle Medicine programs are encouraging.Conclusions. It emerged unequivocally that, taking care and supporting the diabetic subject, leads to significant benefits in the general health and to reduction of possible complications. After the Covid-19 Pandemic, the Nurse Case Manager Lifestyle Medicine could represent a valid alternative of health management for the improvement of care in Type 2 Diabetic patients.